An e-key database system for finfish identification: its design, implementation and utility - Pathak, Ajey Kumar; Singh, Shri Prakash; Chaturvedi, Reeta (Indian Journal of Fisheries, 2017)
electronic keys. Electronic keys of fin formula and other 11 distinguishing characters described for Indian finfishes were prepared and the rule based database approach was implemented to develop the system. In addition to identification, the system provides information on taxonomy and distribution along with photographs of the identified finfish species. The system was built by applying Microsoft Access database and Visual Basic technologies for the Windows platform. The system is interactive to the user through windows components and possesses the ability to correctly identify 837 finfish species belonging to 24 orders and 105 families from fresh (602), brackish (242) and marine waters (323). Out of 837, 83 fishes are common inboth brackish and marine waters. The electronic keys provide the ability to identify any finfish species and provide complete information about the fish species. The system is presently available on Compact Disk (CD) and it was developed assuming the minimum computing (Hardware and Software) resources available to the end users.